Recurrent Aphthous Stomatitis and Related Factors Among 12-17-Year-Old Students in Zahedan, Iran - M shirzaiy; J Sarabadani (Islamic Azad University, 2020)
Background and Aim: Recurrent aphthous stomatitis (RAS) is one of the most common lesions in the oral mucosa. The etiopathogenesis of RAS is not clear. RAS is multifactorial, and several factors can contribute to RAS development. This study aimed to evaluate the RAS prevalence and some related factors in 12-17-year-old schoolchildren in Zahedan City (Southeast of Iran). Materials and Methods: In this descriptive-analytical study, 800 students (12-17 years old) of Zahedan City were examined for the assessment of RAS prevalence and related factors. After filling the questionnaire, oral examinations were done by an oral medicine specialist for RAS prevalence determination. Data were analyzed in SPSS 21 software according to the analysis of variance (ANOVA) and the chi-square test. Results: The RAS prevalence in 12-17-year-old students (400 boys and 400 girls) was 40.7%. The RAS prevalence in girls was significantly higher than that in boys (51% vs 20.5%; P=0.02). RAS had no significant correlation with age or the dominant hand (P˃0.05). Family history of RAS, stress, and trauma from toothbrushing correlated with RAS. The most common location of RAS was the lower lip (29.4%) followed by the mandibular vestibule (19.3%) and the right buccal mucosa (11.58%). Conclusion: RAS prevalence was high among 12-17-year-old students of Zahedan City. Girls were more susceptible to RAS. Age group and the dominant hand did not affect RAS development. It seems that predisposing factors, such as family history of RAS, stress, and trauma from toothbrushing, could contribute to RAS development. The most common location of RAS is the labial mucosa.